2013
DOI: 10.3390/d5030657
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Black Salamanders (Aneides flavipunctatus) across Watersheds in the Klamath Mountains

Abstract: Abstract:Here we characterize the genetic structure of Black Salamanders (Aneides flavipunctatus) in the Klamath Mountains of northwestern California and southwestern Oregon using mitochondrial and nuclear DNA sequences. We hypothesized that the Sacramento, Smith, Klamath, and Rogue River watersheds would represent distinct genetic populations based on prior ecological results, which suggest that Black Salamanders avoid high elevations such as the ridges that separate watersheds. Our mitochondrial results reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 49 publications
2
13
0
Order By: Relevance
“…Tissues were obtained from 240 individuals of Aneides flavipunctatus from 136 localities throughout north-western California and southern Oregon. DNA sequences used in previous molecular studies of A. flavipunctatus (Rissler & Apodaca, 2007;Reilly et al, 2012Reilly et al, , 2013 were downloaded from GenBank (accession numbers: AY274627-AY274756, JX544070-JX544733, KF056387-KF056791). Localities for all specimens used in genetic analysis are presented in Appendix S1 (Fig.…”
Section: Genetic Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissues were obtained from 240 individuals of Aneides flavipunctatus from 136 localities throughout north-western California and southern Oregon. DNA sequences used in previous molecular studies of A. flavipunctatus (Rissler & Apodaca, 2007;Reilly et al, 2012Reilly et al, , 2013 were downloaded from GenBank (accession numbers: AY274627-AY274756, JX544070-JX544733, KF056387-KF056791). Localities for all specimens used in genetic analysis are presented in Appendix S1 (Fig.…”
Section: Genetic Samplingmentioning
confidence: 99%
“…Subsequent work identified contact zones between genetically distinct populations at the Willits/Longvale area of Mendo-cino County, with varying levels of gene flow between the three ecomorphs of the region (Reilly et al, 2012). Additionally, a major genetic break was detected between salamanders in Shasta County and salamanders from the western Klamath Mountains, where gene flow is essentially absent between these populations (Reilly et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…; Reilly et al . ; Reilly & Wake ). Although these topographically complex mountains formed well over 10 Mya, renewed Late Miocene–Pliocene uplifting and restructuring of drainages (Mortimer & Coleman ; Aalto ) may have isolated Uroctonus in the Klamath Mountains from nearby groups to the south and north (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, populations that were founded more recently often have signatures of founder effects or bottlenecks (Theissinger et al 2011, Pessino et al 2014. Previous studies suggest the Klamath-Siskiyou mountains in northern California as a potential Pleistocene glacial refugia for aquatic-associated rough-skinned newts, Pacific giant salamanders, and black salamanders (Kuchta and Tan 2005, Steele and Storfer 2006, Reilly et al 2013. Some studies of salamanders have suggested multiple refugia, including the Columbia River in northern Oregon/Washington (Steele and Storfer 2006) or the Sacramento River in California (Reilly et al 2013).…”
Section: Glacial Legacymentioning
confidence: 99%